Extra-axial central nervous system lesions- a clinicopathological overview - Rangrao Patil, Purwa; Vinod Sondankar, Divyaja; B Mundhe, Mayur (International Journal of Medical Research and Review, 2016)
Background: Extra-axial Central Nervous System (CNS) lesions simply abut the CNS from meningeal or juxtameningeal site and include lesions arising from extra-parenchymal elements in CNS including meninges, nerve sheath or midline neur-axial structures confining to sellar region, pineal region and ventricles. Objective: To study extra-axial CNS lesions in terms of frequency, demography, topography and to assess utility of squash cytology to for their rapid diagnosis. Material and Methods: Total 383 cases of all clinically and radiologically suspected and/or histopathologically confirmed cases of extra-axial CNS lesions were studied with above mentioned objectives and resuls were tabulated and analysed. Result: Extra-axial lesions contributed 49.10% cases of all CNS lesions. Of these extra-axial lesions 68% were neoplastic (benign & malignant) and most of these (86.9%) neoplasms were benign. Neoplastic lesions were most commonly seen in 4th -5th decade while non-neoplastic in 1st-3rd decade with equal sex distribution. They were commonly located intracranially (73.36%) than at spinal location. Meninges were most common affected site. Intracranially meningioma (37.09%) and epidermoid cyst (46.38%) were most common neoplastic and non-neoplastic lesions respectively. While schwannoma (39.59%) and tuberculosis (45.28%) were most common neoplastic and non-neoplastic lesion at spinal location respectively. Extra-axial metastatic neoplasms contributed 2.08% of extra-axial CNS lesions. Developmental anomalies were seen in 19.5% cases. 7.28% neoplastic lesions were recurrent of which maximum were pituitary adenomas. In 74.41% cases radiological diagnosis matched exactly with histopathological diagnosis while squash cytology provided exact diagnosis in 89.84% cases. Conclusion: Extra-axial CNS lesions are common, constituting nearly half of the cases of CNS lesions; most of which are intracranial, slow growing, benign neoplasms and squash cytology plays a great role in intra-operative consultation.